DESKRIPSI JENIS KEKAR DENGAN MENGGUNAKAN APLIKASI DIPS DAN MEGASKOPIS BATUAN BEKU DI GUNUNG BUKITCULA, CIPARAY, KABUPATEN BANDUNG PROVINSI JAWA BARAT - Fadhilla Oktari; Puput Bella Mulbes; Suci Kurniati; Romi Setiawan; Putri Raudatul Jannah; Muhammad Reza Fahlevi; Yovy Irfanolla; Khairunnisa Khairunnisa; Gusti Rahayu; Noveri Mulya; Bigharta Bekti Susetyo (JURUSAN GEOGRAFI FIS UNP, 2020)
This research to determine the number of burly and determine the characteristics of igneous rocks in Bukit Cula. The research method used is descriptive quantitative survey. This research was conducted by using a tool that is a geological compass to determine the direction of the stocky and determine the process of sedimentary rock sampling and igneous description of rocks by megascopically. The results of this study obtained several strike-dip values. The strike-dip data is then processed using DIPS software to produce the Rosette Diagram. DIPS is used to analyze the direction of orientation of geological data that is muscular. In the results of observations made, there were 24 muscular burles. Based on strike-dip measurements on Mount Bukitcula it has a horizontal fault. The igneous rock found in Bukitcula Mountain is a type of andesite igneous rock